Contradictory location of the Black woman passport academic: Embrace, alienation and vulnerability - Maodzwa – Taruvinga, Mandivavarira; Msimanga, Audrey (South African Journal of Higher Education, 2016)
This paper is a narration of two Black women’s experiences and perceptions of inclusion and or exclusion within the academy arising out of their identity as “passport academics”. The inter-relation of nationality, ethnicity and race as identity markers creates power dynamics that lead to conflicting and competing expectations depending on whose discourse holds sway. The competing expectations form the nexus of the contradictory location leading to an identity crisis of a particular kind. Using an auto-ethnographic approach, we describe critical incidences in the course of social and academic relationships within the university which were interpreted as instances of “othering”. Alternate perceptions and feelings of embrace, alienation, and vulnerability by both Black women “passport academics” and Black women South African academics are described. These reveal complex identity issues in which sadly, Black academics’ feelings of affirmation are still seen through the eyes of their White academic colleagues. The irony is that colleagues of different races originating from the same foreign country are often perceived and labelled differently as “outsiders” or “insiders”. It is interesting how one race’s apparent invisibility affords it the privilege of global citizenship while the visibility of Blackness opens one to the scrutiny of national origins. What also emerges is that current discourses of transformation and diversity within the university seem to be struggling under the weight of a nationalistic turn. We conclude by suggesting that recovering the “academic” rather than projecting nationality might be more productive and beneficial to all. Key words: Black woman academic, contradictory location, identity, nationality, passport academic, othering, race, South Africa, university